Estimation of surface PM2.5 with MODIS Aerosol optical depth and source identification using trajectory analysis: A case of Hyderabad City, India - Ashok, Selvetikar; Sekhar, M. Chandra; Reddy, D Rama Bhupal (International Journal of Environment, 2022)
Satellite measurements are important for quantifying the ground observations and atmosphere columnar properties like Aerosol Optical Depth (AOD) especially in developing countries like India. In this study Moderate Resolution Imaging Spectroradiometer (MODIS) retrieval’s AOD product has been used having 3 km and 10 km spatial resolution from terra and aqua satellites, The MODIS AOD data and meteorological parameters from May 2017 to May 2019 were used. The Multiple linear regression method is implemented in this study. The study concluded that there is a good agreement in the prediction of PM2.5 at Zoopark location, whereas in other monitoring locations the agreement between AOD and measured PM2.5 is relatively poor. The particulate matter (PM) concentrations are influenced by the local source regions and the long-range transport of pollutant through the wind, whereas the source regions identified based on the Potential Source Contribution Function (PSCF), Concentration-Weighted Trajectory (CWT) and Cluster analysis indicate the dominant source regions. Results indicate that the Central India and East Indian regions are more dominating source regions at Hyderabad location in the winter season. It was found that the lower altitude layer showed the major source of local regions nearby receptor. The cluster analysis indicates that the high intensity from the East Indian regions. This paper not only demonstrates reasonable prediction accuracy but also provides the model uncertainties which lays foundation for further study.